Conversion and characterization of Bio-Coke from abundant biomass waste in Malaysia. (December 2020) - Kamal Baharin, Nur Syahirah; Koesoemadinata, Vidya Cundasari; Nakamura, Shunsuke; Yahya, Wira Jazair; Muhammad Yuzir, Muhamad Ali; Md Akhir, Fazrena Nadia; Iwamoto, Koji; Othman, Nor'azizi; Ida, Tamio; Hara, Hirofumi
Abstract: Depletion of fossil fuels and the adverse impacts burning these fuels has increased the attention towards utilizing biomass energy sources, thus increasing the focus on Bio-Coke technology, which can fully convert biomass waste into alternative fuels. This study analyzed the characteristics of Bio-Coke conversion from biomass abundantly found in Malaysia, which included rice husk, rubber wood sawdust, coconut husk, sugarcane bagasse, oil palm frond, oil palm trunk and empty fruit bunch (EFB). Results indicated better physical feature characteristics of biomass solid fuel. For example, Bio-Coke produced from EFB showed an apparent density of 1.414 g/cm 3, combustion duration of 1664 s, and maximum compressive strength at room temperature (25 °C) and 700 °C of 95.107 and 9.412 MPa, respectively, which were found to be higher than that of wood pellet. This study showed Bio-Cokes can be potentially used as an alternative fuel to reduce the usage of coal coke in the future. Highlights: Bio-Cokes were produced from eight different types of abundant biomass in Malaysia. Bio-Coke has a high retention of biomass energy as no weight lost during production. Bio-Coke by EFB showed better features than pellet and comparable with Coal Coke. Bio-Coke production showed high potential strategies for the alternative solid fuel.